PELAKSANAAN SUPERVISI AKADEMIK KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU PADA MADRASAH IBTIDAIYAH SWASTA (MIS) SINGKARAK KABUPATEN SOLOK - Joni Joni (IAIN Batusangkar, 2016)
This study aimed at describing the implementation of the headmaster’s academic supervision on upgrading teachers’ performance in Islamic Primary School Singkarak, Solok. The interview and documentation were used as insturments to collect data. The results revealed that the supervision was run well, the headmaster did usual supervision and clinical supervision on upgrading the teachers’ performance.Keywords: Headmaster, Supervision, Teachers’ Performance, Islamic Primary School Singkarak, Solok